Brief Report: Increased Inflammation and Liver Disease in HIV/HBV-Coinfected Individuals. (1st November 2021) - Copeland, Nathanial K.; Eller, Michael A.; Kim, Dohoon; Creegan, Matthew; Esber, Allahna; Eller, Leigh Anne; Semwogerere, Michael; Kibuuka, Hannah; Kiweewa, Francis; Crowell, Trevor A.; Polyak, Christina S.; Ake, Julie A.
Abstract : Objective: HIV and hepatitis B virus (HBV) coinfection can accelerate morbidity and mortality, especially in sub-Saharan Africa where both infections are common. Although inflammation contributes to disease progression, more information is needed to better understand the pathology. This study compared markers of cirrhosis and inflammation in HIV/HBV-coinfected individuals compared with monoinfected and uninfected patients. Setting: The HIV/HBV-coinfected subjects from the Ugandan arm of the prospective African Cohort Study were selected for evaluation and matched by age and gender with HIV-monoinfected, HBV-monoinfected, and uninfected controls. Methods: Plasma samples were used to quantify markers of immune activation and inflammation. The FIB-4 (a simple index to predict significant liver fibrosis) score was used to estimate liver fibrosis. Demographic and laboratory characteristics were compared across the groups. Results: Together, 31 HIV/HBV-coinfected participants were identified and compared with 62 HIV-monoinfected, 7 HBV-monoinfected, and 62 uninfected controls. The HIV/HBV-coinfected group had generally higher levels of inflammation. Most notably, matrix metalloproteinase-2, matrix metalloproteinase-9, and fibroblast growth factor-19 levels were dysregulated among the HIV/HBV-coinfected individuals. Furthermore, the FIB-4 score was higher in the HIV/HBV-coinfected group compared with the HIV-monoinfected group and revealed that 11% of HIV/HBV-coinfected individuals had evidence of undiagnosed advanced liver disease. Conclusions: Differences in levels of inflammation exist between individuals with HIV/HBV coinfection compared with monoinfected and uninfected controls. A distinct signature of inflammation was associated with HIV/HBV coinfection that could reflect the mechanism of liver fibrosis and increased risk for disease progression. Finally, there may be an underappreciated amount of undiagnosed advanced liver disease in sub-Saharan Africa. Abstract : Supplemental Digital Content is Available in the Text.